Gastrobronchial Fistula: A Rare Complication of Postlaparascopic Sleeve Gastrectomy—A Case Report and Literature Review - Mohammed Sabawi; Alhassan Alhasson; Abdul-Rahman Abualruz; Alaa Abdulsattar Al-Taie (Case Reports in Radiology)
Introduction. Obesity is one of the leading causes of morbidity and mortality in countries all over the world, and its prevalence has been increasing dramatically in recent years. Bariatric surgery is considered the gold standard of care for patients who failed conservative management. Laparoscopic sleeve gastrectomy (LSG) is of increasing popularity. One of its vicious consequences is the development of acquired fistula between the stomach and the tracheobronchial tract due to intractable gastric leak. Case Report. We are presenting a case of a 25-year-old man who underwent laparoscopic sleeve gastrectomy for morbid obesity, which was complicated with the development of gastrobronchial fistula, despite an unremarkable postoperative course. Conclusion. Acquired gastrobronchial fistula due to bariatric surgery is not reported widely in radiologic literature; hence, there is lack of consensus of the diagnostic modality of choice. However, there is a myriad of tests available for diagnosing gastrobronchial fistula, with contrast study of the upper gastrointestinal tract which is the widely accepted diagnostic test.